Representasi Budaya Sasak dalam Begawe Pati di Kecamatan Batukliang Utara: Kajian Antropolinguistik - Dewi Hafidayanti; Muhammad Sukri; Saharudin (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
The ritual of begawe pati 'feast for the dead' in Batukliang Utara District as a form of farewell carried out by living relatives towards the deceased. In the begawe pati there are many linguistic lingual units used to mark the language in begawe pati. The purpose of this study was to determine the lingual units contained in begawe pati in Batukliang District. This study is a qualitative descriptive study. This study uses observation, interview, and documentation methods with note- taking techniques. The results of this study found that the lingual units related to begawe pati with the order of lingual units in the form of words, lingual units in the form of verbs, lingual units in the form of phrases, and lingual units in the form of clauses. Meanwhile, from the cultural perspective on begawe pati, the local community views begawe pati as a series of events in the Sasak traditional death ceremony which in ancient times was a form of respect for the deceased so that they would be calm on their journey to the next world, in addition so that the bereaved family could sincerely let go of the deceased. The community believes that the rituals contained in begawe pati are worthy of being passed on to their successors because they do not harm others and insult the teachings of Islam.